Keadilan Distributif dan Peran Negara Menurut M. Umer Chapra: Analisis Terhadap Konsep dan Implementasinya - Rachma Febriyanti; Bin Sapa, Nasrullah (JSE: Jurnal Sharia Economica, 2025)
The post-1980 dominance of neoliberal economics has exacerbated structural inequalities, while socialism failed to address efficiency challenges. In this context, M. Umer Chapra’s ideas on distributive justice and the state’s role offer a value-based Islamic alternative. This article critically examines Chapra’s framework through qualitative library research, employing content analysis of his seminal works (Islam and the Economic Challenge, The Future of Economics). The study reveals that Chapra rejects the capitalism-socialism dichotomy and proposes an Islamic economic system anchored in: (1) preventive-curative justice (via zakat, equitable taxation, and prohibition of riba); (2) the state as an ethical facilitator in market regulation and wealth redistribution; and (3) the integration of maqasid al-shariah (higher objectives of Islamic law) as a policy blueprint. These ideas remain relevant to contemporary crises, including global inequality and ecological degradation, yet their implementation requires bold institutional reforms. By elucidating the practical dimensions of Chapra’s thought, this article advances Islamic economics literature beyond theoritical discourse toward actionable policy design.